XC endurance training theory - Norwegian style - Part I - Seiler, S.; Skjaerli, B. (2002)
A training intensity chart is presented, which is a closely patterned after the basic intensity classifications for endurance training used by XC skiers and trainers in Norway. When they denote training intensity, this is the language used. Author has added another column: lactate concentration. These values are based on several sources including long term studies of elite rowers in Germany. Autor thinks rowing and XC are very similar because they are both quadripedal exercise modes.